Modeling infinitely many agents - Wei He; Xiang Sun; Yeneng Sun (Theoretical Economics, 2017)
This paper offers a resolution to an extensively studied question in theoretical economics: which measure spaces are suitable for modeling many economic agents? We propose the condition of 'nowhere equivalence' to characterize those measure spaces that can be effectively used to model the space of many agents. In particular, this condition is shown to be more general than various approaches that have been proposed to handle the shortcoming of the Lebesgue unit interval as an agent space. We illustrate the minimality of the nowhere equivalence condition by showing its necessity in deriving the determinateness property, the existence of equilibria, and the closed graph property for equilibrium correspondences in general equilibrium theory and game theory.
Keywords: C7; D0; D5; 330; Agent space; nowhere equivalence; Nash equilibrium; Walrasian equilibrium; determinateness property; closed graph property; relative saturation; atomless independent supplement; conditional atomlessness